2016
DOI: 10.1121/1.4945746
|View full text |Cite
|
Sign up to set email alerts
|

Audibility of dispersion error in room acoustic finite-difference time-domain simulation as a function of simulation distance

Abstract: Finite-difference time-domain (FDTD) simulation has been a popular area of research in room acoustics due to its capability to simulate wave phenomena in a wide bandwidth directly in the time-domain. A downside of the method is that it introduces a direction and frequency dependent error to the simulated sound field due to the non-linear dispersion relation of the discrete system. In this study, the perceptual threshold of the dispersion error is measured in three-dimensional FDTD schemes as a function of simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…There is no significant difference between the distributions of the observations in the different distance groups. The maximum group delay values agree with the findings of the previous threshold study, 2 where the mean value of the measured maximum group delay value was found to be 1.8 ms.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There is no significant difference between the distributions of the observations in the different distance groups. The maximum group delay values agree with the findings of the previous threshold study, 2 where the mean value of the measured maximum group delay value was found to be 1.8 ms.…”
Section: Discussionsupporting
confidence: 82%
“…The selection of a single scheme is justified with the result presented in Ref. 2, that with schemes with a similar phase velocity error contour, the audibility of the error as function of distance is similar. Therefore, in order to reduce the number of trials, only a single scheme condition is used.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In Fig. 10, we plot (k X ) for various schemes (leaving out some large-star schemes, for clarity); and we focus on (k X ) ≤ 5%-for brevity, and because there is recent evidence that high-fidelity auralizations require phase velocities errors to be as low as 2% to mitigate audible phase artifacts [18]. From Fig.…”
Section: C O M Pa R I S O N S : N U M E R I C a L D I S P E R S I O Nmentioning
confidence: 99%
“…Digital Object Identifer 10.1109/TASLP.2017.00000000 audible phase artifacts [18]. Mitigating such effects through grid oversampling incurs significant additional computational costs and therefore is not always practical for large-scale simulations.…”
Section: Introductionmentioning
confidence: 99%